Tinjauan Yuridis Empiris Mengenai Uang Pengganti Dan Keharusan Membayar Dalam Kasus Tindak Pidana Korupsi - Kurniawan, Rocky Bagus; , Dr. Natangsa Surbakti, S.H., M.Hum; , Muchamad Iksan,S.H., MH (2016)
Money charge conviction is the consequence of criminal acts of corruption which might put the state finance or economy suffers. Juridical measure is a necessity in order to restore the detriment of the state in the form of penalty. The concept of penalty charge is to punish the perpetrators of corruption with an eye to they will not able in using the money and the country can obtain restitution. This research uses descriptive juridical empiric approach with the type of primary data and secondary data. They are collected through the study of literature, interviews, and observation by using qualitative data analysis. Based on the results of research and discussion, it can be concluded that corruption is an act against law and could harm the state finances. Thus the detriment of the state must be restored from the perpetrators. The way to reimburse it is by imposing the defendant who is proven and convincingly guilty of corruption to give back to the state in the form of restitution. Crime provisions for such penalty in cases of corruption lies in the Act No. 20 of 2001 on amendments of Act No. 31 of 1999 on Corruption Obliteration. In Article 18 Paragraph 1 letter b stated that the perpetrators of corruption can be sentenced to an additional form of penalty, a sum which is equal to the amount of wealth derived from corruption.